Extractive Industries and Sustainable Development : An Evaluation of World Bank Group Experience - Liebenthal, Andrés; Michelitsch, Roland; Tarazona, Ethel (Washington, DC: World Bank, 2012)
This evaluation finds that with its global mandate and experience, comprehensive country development focus, and overarching mission to fight poverty, the World Bank Group is well positioned to help countries overcome the policy, institutional, and technical challenges that prevent them from transforming resource endowments into sustainable benefits. Furthermore, the World Bank Group's achievements are many. On the whole, its extractive industries projects have produced positive economic and financial results, though compliance with its environmental and social safeguards remains a challenge. Its research has broadened and deepened understanding of the causes for the disappointing performance of resource-rich countries. Its guidelines for the mitigation of adverse environmental and social impacts have been widely used and appreciated. More recently, it has begun to address the challenge of country governance with a variety of instruments.